Connoisseur kids : ettiquette, manners, and living well for little ones - Scott, Jennifer L. (Jennifer Lynn) (Chronicle Books, 2019)
"Jennifer Scott is the powerhouse behind the internationally best-selling series of Madame Chic books about how to live with the grace and elegance of a Frenchwoman. In Connoisseur Kids, her departure from the Madame Chic publishing, she presents the do's and don'ts of raising responsible, civilized, well-behaved children who are a pleasure to be around. In 5 chapters detailing the basics of manners, hygiene, being neat, and physical and emotional health, children ages 4 to 7 will be equipped to be good citizens of the world through rhymes and songs, hands-on activities, and lovely illustrations. Authoritatively curated by a mother of 3 recognized for her social graces, the content includes must-know guidance for everyday life (please and thank yous, table manners, listening), social protocols (thank-you cards, listening), as well as tidy habits for their rooms, possessions, and tiny bodies. Packaged in a gifty, full-color hardcover, and featuring an engaging introduction on the importance of creating a harmonious family life, this is irresistibly chic and charming reference at its gifty best"--